Investigation on Abradability of Nickel - Graphite Coatings under aSimulated Service Condition - GAO Dong, Wang Jing, GUO Yun-shan, QIAN Ling-yi (Cailiao Baohu, 2021)
Flame sprayed nickel-graphite sealing coatings are widely used on the high pressure compressor (HPC) front start-up box forward case assembly and other aircraft engine parts, with the purpose of controlling the clearance between the rotors and surrounding casing by friction with the blade tips or labyrinth, thus to improve the efficiency of the engine and lower the specific fuel consumption, and the abradability is the one of the most important properties to evaluate the property of the sealing coating. In the present paper, according to the urgent requirements of aeroengine design, the friction and wear test of nickel-graphite coating under simulated working conditions was carried out, the abradability of the coating was deeply studied, and the influence mechanism of cutting depth and cutting rate on the abradability of the coating was analyzed. Results indicated that the effect of incurs depth on wearing of the coating was more significant than that of the incursion rate at the same blade tip linear speed. The dominant friction and wear mechanisms of the nickel-graphite coating at high linear velocity were plastic deformation and friction oxidation. The environmental temperature had a certain influence on the friction and wear of the coating.